Review paperRecording of the neuronal activity in the gastrointestinal tract using the Multisite Optical Recording Technique (MSORT) - Ceregrzyn, Michał; Michel, Klaus; Schemann, Michael (Archives of Medical Science, 2005)
The Enteric Nervous System (ENS) plays a key role in regulating the function of the gastrointestinal tract. The knowledge about the function of neurons is based on experiments using the intracellular recording method. Limitations of the method have become a stimulus for developing an alternative technique that would record cell membrane potential changes without mechanical interruption and with no cells bias due to their size. The recently developed neuroimaging method meets these demands. The principle of the technique is based on fluorescence of voltage sensitive dyes (VSD) specific molecules that incorporated in cell membranes react to their potential. Photodiode arrays or charge-coupled device (CCD) cameras can be used for acquiring the fluorescent light that permits to monitor fast changes in membrane potential. The Multisite Optical Recording Technique (MSORT) is capable of recording changes in membrane potential in all neurons in the ENS with sufficient spatial and temporal resolution. Studies published up to date are very promising and give an interesting view on the function of neurons in the ENS.